Positive and negative regulation of Fc epsilon receptor I-mediated signaling events by Lyn kinase C-terminal tyrosine phosphorylation - Tolar, Pavel; Dráberová, Lubica; Tolarová, Helena; Dráber, Petr (European journal of immunology, 2004)
Although it is known that the Src family tyrosine kinase Lyn initiates Fc epsilon receptor I (Fc epsilon RI) signaling by phosphorylation of the receptor subunits, regulation of Lyn kinase activity and its consequences for receptor signaling are incompletely understood. Using a phospho-Lyn-specific antiserum, we show an increased phosphorylation of the Lyn C-terminal regulatory tyrosine and decreased Lyn kinase activity during Fc epsilon RI-mediated mast cell activation. Mutant Lyn, defective in the C-terminal tyrosine, constitutively phosphorylated several substrates in resting cells, but did not cause Fc epsilon RI internalization or spontaneous degranulation. Fc epsilon RI-induced signaling in the presence of constitutively active Lyn exhibited enhanced phosphorylation of the receptor subunits, Syk, LAT, Gab2, phospholipase C (PLC)gamma 1 and PLC gamma 2, and production of phosphatidylinositol 3,4,5-trisphosphate. Although enzymatic activities of PLC gamma 1 and PLC gamma 2 were also up-regulated, amounts of inositol 1,4,5-trisphosphate, mobilization of intracellular calcium and degranulation were suppressed. Additionally, constitutively active Lyn was strikingly less efficient than wild-type Lyn in restoring the receptor-mediated calcium responses in bone marrow mast cells derived from Lyn(-/-) mice. These findings pinpoint the tight regulation of Lyn kinase activity as a critical event in mast cell degranulation.
Keywords: Cells, Cultured; Receptors, IgE; zvířata; test degranulace bazofilů; Tyrosine; fosforylace; kultivované buňky; receptory IgE; Basophil Degranulation Test; src-Family Kinases; Animals; tyrosin; signální transdukce; Signal Transduction; Mast Cells; mastocyty; Phosphorylation; skupina kinas odvozených od src-genu